1977
DOI: 10.1126/science.929191
|View full text |Cite
|
Sign up to set email alerts
|

Fascioliasis: Role of Proline in Bile Duct Hyperplasia

Abstract: In animals fascioliasis, extensive hyperplasia of the main bile duct occurs that often results in enlargement of the duct to more than 20 times the normal. We report that proline infused into the abdominal cavity of rats caused hyperplasia of the bile duct resembling that produced in the early stages of the disease. We suggest that Fasciola hepatica, which synthesizes and releases large amounts of proline, induces enlargement of the bile duct by a similar mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…In the biliary stage, ultrasound seems to be more useful, and may show biliary dilation and especially bile duct wall thickening, suggesting biliary fascioliasis. Adult flukes, either due to a direct irritating effect or perhaps to the induction of a high proline concentration in the bile, promote hyperplasia and hypertrophy of the duct epithelium and enveloping periductal fibrosis, resulting in thickening of the duct walls (20). A significant sonographic finding for fascioliasis is that dilated bile ducts are filled with nonshadowing material isoechoic to the liver.…”
Section: Discussionmentioning
confidence: 95%
“…In the biliary stage, ultrasound seems to be more useful, and may show biliary dilation and especially bile duct wall thickening, suggesting biliary fascioliasis. Adult flukes, either due to a direct irritating effect or perhaps to the induction of a high proline concentration in the bile, promote hyperplasia and hypertrophy of the duct epithelium and enveloping periductal fibrosis, resulting in thickening of the duct walls (20). A significant sonographic finding for fascioliasis is that dilated bile ducts are filled with nonshadowing material isoechoic to the liver.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, excess proline administered via intraperitoneal infusion causes bile duct hyperplasia in rats and mice [20-241 and the proline analog, azetidine, inhibits bile duct hyperplasia in Fasciola hepatica implanted rats [25]. Both human and animal liver flukes cause enlargement and hyperplasia of bile duct as well as periductal fibrosis [ 1-15,17,2G25] and it has been suggested that induction of bile duct hyperplasia by proline might occur in other liver fluke diseases, including opisthorchiasis [20]. Therefore, proline might itself act as a promoter in driving initiated bile duct cells to tumors [4,5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Isseroff et al [117] first provided evidence to indicate that the exten sive hyperplasia of the main extrahepatic duct of rats infected with the liver fluke Fasciola hepatica is related to the production of large amounts of proline by this parasite [117], When E-proline was infused into rats [117] and mice [118], it was shown to elicit a hyperplasia of the extrahepatic bile duct epithelium, but in mice at least, did not induce intrahepatic bile ductal or ductular cell proliferation [118]. L-Proline, as a single factor, was not found to stimulate DNA synthesis in primary cul tures of intact intrahepatic bile ducts from normal rats [99] and in primary monolayer cultures of intrahepatic bile ductular epithelial cells from bile duct-ligated rats [Mathis and Sirica, unpublished data].…”
Section: Growth Properties Of Biliary Epithelial Cells and Oval Cellsmentioning
confidence: 99%